2014
DOI: 10.1115/1.4026457
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Regional Adaptations in the Growing Pulmonary Artery Using a Meso-Scale Structural Model: Effects of Ascending Aorta Impingement

Abstract: As the next step in our investigations into the structural adaptations of the main pulmonary artery (PA) during postnatal growth, we utilized the extensive experimental measurements of the growing ovine PA from our previous study (Fata et al., 2013, "Estimated in vivo Postnatal Surface Growth Patterns of the Ovine Main Pulmonary Artery and Ascending Aorta," J. Biomech. Eng., 135(7), pp. 71010-71012). to develop a structural constitutive model for the PA wall tissue. Novel to the present approach was the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…To statistically compare the degree of anisotropy between the normo- and hypertensive states, the differences between maximum values of S LL and S CC were computed from the interpolated equi-biaxial response, in which E LL = E CC (19,46). A larger difference would indicate a higher degree of anisotropy, i.e., the stress-strain responses along the longitudinal and circumferential directions would follow distinctly different paths.…”
Section: Methodsmentioning
confidence: 99%
“…To statistically compare the degree of anisotropy between the normo- and hypertensive states, the differences between maximum values of S LL and S CC were computed from the interpolated equi-biaxial response, in which E LL = E CC (19,46). A larger difference would indicate a higher degree of anisotropy, i.e., the stress-strain responses along the longitudinal and circumferential directions would follow distinctly different paths.…”
Section: Methodsmentioning
confidence: 99%
“…(1) From the native tissue mechanical data, predict the collagen phase parameters ðh c , m G , sG, m 0 , s 0 Þ using standard procedures [33,63]. We found that this basic sequence ensured a robust parameter is obtained, because the entire model is never fitted at once.…”
Section: Parameter Estimation Proceduresmentioning
confidence: 99%
“…The cell-network system was stretched by different amounts (5,10,15,20,25,30,35,40,45,50, 55 and 60% strain) before remodelling. The system was stretched uniaxially and incompressibility was enforced.…”
Section: System Deformationmentioning
confidence: 99%
“…Significant strides have been made through the use of theoretical models that treat the cells and ECM as a continuum (e.g. [18][19][20][21][22]). In particular, many models invoke the concept of tensional homeostasis, in which cells grow and/or modify the ECM to achieve a target stress.…”
Section: Introductionmentioning
confidence: 99%